The use of body mechanics principle, clinical-practice fatigue, and practice satisfaction of nursing students. (2017) - Kang, Se-Won
Abstract: Purpose: The purpose of this study is to investigate the relations among the use of the body mechanics principle, clinical-practice fatigue, and practice satisfaction of nursing students. Methods: Participants were 149 nursing students with clinical-practice experience from four nursing colleges in South Korea. Data were collected from May to July of 2016 using structured questionnaires. The collected data were analyzed using PASW Statistics 22.0. Results: The participants' scores for the use of body mechanics principle, clinical-practice fatigue, and practice satisfaction were 3.12 (out of 5), 4.61 (out of 7), and 3.58 (out of 5), respectively. The use of the body mechanics principle and clinical-practice fatigue showed a negative correlation ( r =−0.379, p <0.001) while the use of the body mechanics principle and practice satisfaction showed a positive correlation ( r =0.341, p <0.001). Clinical-practice fatigue and practice satisfaction showed a positive correlation ( r =−0.384, p <0.001). The group of students who scored high on the use of the body mechanics principle showed significantly lower scores on clinical-practice fatigue than those who scored low on the use of the body mechanics principle (t=3.879, p <0.001) while the scores on the satisfaction of clinical practice were significantly high (t=−3.338, p <0.001). Conclusions: This study found that nursing students' use of the body mechanics principle could reduce clinical-practice fatigue and increase practice satisfaction. It is necessary to develop and teach various body mechanics programs for nursing students. Highlights: Improper working posture increases the risk of damage to the body. It is necessary to educate nursing students at the start of their training on the use of the body mechanics principle. The use of the body mechanics principle could reduce clinical-practice fatigue, and increase practice satisfaction. It is also necessary to consistently educate nursing students on the use of the body mechanics principle.